Repeated heart rate variability monitoring after myocardial infraction – Cohort profile of the MI-ECG study - Teemu Pukkila; Jani Rankinen; Leo-Pekka Lyytikäinen; Niku Oksala; Kjell Nikus; Esa Räsänen; Jussi Hernesniemi (International Journal of Cardiology: Heart & Vasculature)
The purpose of this study was to monitor heart rate variability (HRV) parameters after myocardial infarction (MI), addressing the ongoing controversy regarding their prognostic value. HRV was measured via Holter monitoring during the acute phase around the time of discharge and again two weeks later during recovery. Our findings show that HRV parameters remained stable during the initial weeks post-MI, indicating that the timing of Holter monitoring in this period is not critical.Several HRV parameters were significantly correlated with MI type, Killip class, and left ventricular ejection fraction (LVEF), with reduced HRV observed in STEMI patients and those with decompensated heart failure. However, after adjusting for GRACE score and LVEF, the prognostic value of most HRV measures for predicting future cardiac events diminished. Notably, detrended fluctuation analysis DFA1 α2 yielded a significant hazard ratio (HR) of 0.79 when adjusted for the GRACE score. However, this significance diminished after adjusting for LVEF (HR = 0.84).In conclusion, HRV parameters reflect MI severity and correlate with clinical characteristics, but their independent predictive value for future cardiac events is limited when adjusted for established risk factors such as LVEF and GRACE score.